THE IMPORTANCE OF “ARTEDU+” ART TECHNOLOGY IN DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE DIRECTORS (Conferencea, 2024)
This article discusses the importance of using “ArtEdu+” art technology in developing the professional competence of future directors. It covers the stages of implementing art technology, its forms, methods, and tools, as well as the objectives and tasks of art technology.